Estri celuloze s sulfonskimi kislinami - Rep, Gregor (Les (Ljubljana), 2002)
Altering the molecular structure of natural polymers enables development of new materials with special properties. Cellulose sulfonates, especially tosylates, have been used as intermediates for further functionalization of cellulose. Tosylate groups can be easily replaced by various nucleophiles to yield derivatives that cannot be prepared directly. On the other hand, tosylate groups may serve as protecting groups in subsequent modifications of the remaining hydroxyl groups.
Keywords: estri; celuloza; sulfoniranje; toziliranje